Mehmet Gün (2020) Turkey’s Middle-Democracy Issues and How to Solve Them: Judiciary, Accountability and Fair Representation - Çınar, Özgür H. (Border Crossing, 2020)
This is a book review on Mehmet Gün, Turkey’s Middle-Democracy Issues and How to Solve Them: Judiciary, Accountability and Fair Representation. For many years, Turkey has had a poor record as regards human rights. Despite Turkey being a signatory to international conventions on human rights it has not consistently safeguarded these rights. Turkey made some progress by introducing reforms that began with the European Union (EU) accession process initiated in 1999. This process ushered in harmonisation laws and implementation of judgments of the European Court of Human Rights (ECtHR) that led to developments on the normative level. However, these changes were not sufficiently put into practice or adopted by public mechanisms.